2020
DOI: 10.35791/jteta.11.1.2020.29981
|View full text |Cite
|
Sign up to set email alerts
|

Kajian Irigasi Mikro Pada Sistem Hidroponik Padi (Oriza Sativa L.) Varietas Serayu Dalam Rumah Tanaman

Abstract: The purpose of this study was to examine the effect of the thickness of irrigation water flow in the Deep Flow Technique (DFT) hydroponic system on the amount of plant water requirement (or evapotranspiration) and the Water Use Efficiency (WUE) in rice cv. Serayu at the vegetative phase. This research was carried out in a tropical greenhouse roofed with polyethylene (PE) plastic film. The treatments in this study were three kinds of thickness of  micro irrigation in the DFT hydroponic system, i.e. 2, 4 and 6 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
1
1
Order By: Relevance
“…17 ± 1.94 g/planting hole, or equivalent to 33.6 tons/ha/year of fresh weight. This result is still lower than the research results reported by Moningka et al (2020), where at the same age it produced a fresh weight of 62.46 g/planting hole. This could be due to differences in nutrition, variety, temperature, or humidity (Rosliani and Sumarni, 2005) variety factor had no significant effect, the IR64 variety produced a heavier plant canopy than the Ciherang variety.…”
Section: Weight Of Race Plantscontrasting
confidence: 74%
“…17 ± 1.94 g/planting hole, or equivalent to 33.6 tons/ha/year of fresh weight. This result is still lower than the research results reported by Moningka et al (2020), where at the same age it produced a fresh weight of 62.46 g/planting hole. This could be due to differences in nutrition, variety, temperature, or humidity (Rosliani and Sumarni, 2005) variety factor had no significant effect, the IR64 variety produced a heavier plant canopy than the Ciherang variety.…”
Section: Weight Of Race Plantscontrasting
confidence: 74%
“…Benih padi disemaikan pada lahan hingga berumur 25 HSS (Shaibur et al 2008), ditanam 2 bibit padi di setiap netpot (Sutrisna et al 2018), menyulam tanaman yang tidak tumbuh atau kondisinya abnormal pada 7-14 HST (Moningka et al 2020), melakukan irigasi berselang dengan menguras air dalam bak ketika sore hari (17.00 WIB) dan mengembalikan air dalam bak ketika pagi hari (07.00 WIB) pada fase vegetatif saat tanaman berumur 16-46 HST (Budianto et al 2020), memberikan nutrisi AB mix sesuai dengan kebutuhan tanaman (Moningka et al 2020), mengukur Electric Conductivity/EC (500-1500 µS/cm pada fase vegetatif dan 1500-3000 µS/cm pada fase generatif) dan pH media 6,5-7 agar unsur hara terserap dengan baik (Qurrohman & Ginandjar 2018), menambahkan air pada bak tanam untuk mengganti volume air yang hilang akibat evapotranspirasi (Moningka et al 2020), mengendalikan organisme pengganggu tanaman (OPT) berdasarkan hasil pemantauan di lapangan (Sutrisna et al 2018), dan memanen padi ketika tanaman telah memenuhi syarat untuk siap-panen.…”
Section: Prosedurunclassified
“…A hydroponic system is seen as an alternative rice cultivation system that possibly be able to resolve these biophysical-related issues. However, there is other factors should be considered as alternative cultivation system which include planting media and nutrient concentration [3,6], thickness of the micro irrigation in DFT system [4], container size and nutrients used [5].…”
Section: Introductionmentioning
confidence: 99%